2005
DOI: 10.1002/mrd.20385
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Serpinb6 serpins in germ and somatic cells of mouse gonads

Abstract: The serpin superfamily of serine protease inhibitors is implicated in the regulation of numerous physiological processes. In mice, Spi3/Serpinb6 has a broad tissue distribution. We have investigated the expression of Serpinb6 family members in embryonic and adult gonads. In male and female mice, Spi3/Serpinb6 and NK13/Serpinb6b were expressed in developing gonads and in both somatic and germ cells of adult gonads. By contrast, gonadal expression of Spi3C/Serpinb6c was sexually dimorphic and restricted to male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This phenomenon is clearly reflected by the gene networks of Jun and Cebpb in particular: most of their target genes which show increased or even specific signals in AMH-Cre Sox9 flox/flox testes (such as C3ar1 , Cd44 , Cd14 , Cebpa , Cxcl13 , H2-Aa , Icam1 , Ildr2 , Ly6d , Maob , Nupr1 , and Prdx1 ) are involved in immunological or inflammatory processes (see Mouse Genome Database for references). Interestingly, we also observed loci that play roles in down-regulating the immune response which likely reflects a stress response mechanism activated in increasingly damaged testicular tissue: for example, we found two serine protease inhibitors Serpinb6b (Serine (or cysteine) peptidase inhibitor, clade B, member 6B) and Serpina3n , [61], which are known to act on Granzymes A and B proteases secreted by cytotoxic T-lymphocytes [62,63]. Cultured human Sertoli cells - which are perhaps in a similar state of stress as Sox9 -negative Sertoli cells in degenerating testicular tissue - secrete Serpina3n which was found to bind and inhibit Granzyme B, revealing a direct mechanism of Sertoli cell-dependent immunoprotection [64].…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon is clearly reflected by the gene networks of Jun and Cebpb in particular: most of their target genes which show increased or even specific signals in AMH-Cre Sox9 flox/flox testes (such as C3ar1 , Cd44 , Cd14 , Cebpa , Cxcl13 , H2-Aa , Icam1 , Ildr2 , Ly6d , Maob , Nupr1 , and Prdx1 ) are involved in immunological or inflammatory processes (see Mouse Genome Database for references). Interestingly, we also observed loci that play roles in down-regulating the immune response which likely reflects a stress response mechanism activated in increasingly damaged testicular tissue: for example, we found two serine protease inhibitors Serpinb6b (Serine (or cysteine) peptidase inhibitor, clade B, member 6B) and Serpina3n , [61], which are known to act on Granzymes A and B proteases secreted by cytotoxic T-lymphocytes [62,63]. Cultured human Sertoli cells - which are perhaps in a similar state of stress as Sox9 -negative Sertoli cells in degenerating testicular tissue - secrete Serpina3n which was found to bind and inhibit Granzyme B, revealing a direct mechanism of Sertoli cell-dependent immunoprotection [64].…”
Section: Discussionmentioning
confidence: 98%
“…In our present study, in situ hybridization and immunohistochemistry revealed that mRNA and protein localization of SERPINB6 was restricted only to the GCs of bovine follicles. It has been demonstrated that Spi/SERPINB6, which is the mouse ortholog of SERPINB6, and two Spi3/SERPINB6 paralogs, NK13/SERPINB6b and Spi3C/SERPINB6c, were expressed in a mouse follicular somatic cells and/or oocytes [45]. A primary target protease of SERPINB6 is cathepsin G [46], whereas its gene expression is likely to be restricted to the myeloid lineage [47] while the expression in ovarian follicular cells is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As tPA is overexpressed in cultures, the levels of these conjugates would be low relative to the total tPA and therefore would not be expected to significantly reduce the bioactivity of the tPA in vitro or in vivo. Interestingly, Serpin B6 is high in gonadal tissues, so it is perhaps not surprising that it is expressed in Chinese hamster ovary cells …”
Section: Case Studiesmentioning
confidence: 99%